1999
DOI: 10.1029/1999wr900158
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy, lacunarity, and upscaled conductivity and its autocovariance in multiscale random fields with truncated power variograms

Abstract: Abstract. It has been shown by Di Fededco and Neuman [1997, 1998a, b] that observed multiscale behaviors of subsurface fluid flow and transport variables can be explained within the context of a unified stochastic framework, which views hydraulic conductivity as a random fractal characterized by a power variogram. Such a random field is statistically nonhomogeneous but possesses homogeneous spatial increments. Di Federico and Neuman [1997] have demonstrated that the power variogram and associated spectra of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 29 publications
4
84
0
Order By: Relevance
“…In addition to the experimental approach cited above, some authors proposed theoretical methods to generate the k variation with the scale, utilizing statistical procedures (Di Federico and Neuman, 1997;Di Federico et al, 1999) or, in other circumstances, utilizing the fractal theory (Davy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the experimental approach cited above, some authors proposed theoretical methods to generate the k variation with the scale, utilizing statistical procedures (Di Federico and Neuman, 1997;Di Federico et al, 1999) or, in other circumstances, utilizing the fractal theory (Davy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, such a large number of experiments have reported an increase in K with increasing scale [8][9][10][11][12][13][14][15][16][17][18][19][20] that it becomes necessary to find an explanation for such effects. Some researchers have sought to find theoretical explanations of such an effect [21][22][23][24]. Some of these experimental results are contested by other researchers, based on a critique of either the analysis or the experimental conditions [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of regional-scale transport characteristics must incorporate smaller-scale variability into models of the system (some examples of upscaling methods include Gelhar and Axness 1983;Li et al 1994;Haggerty and Gorelick 1995;Berkowitz et al 2000;Haggerty et al 2000). Studies have shown that accurate upscaled transport modeling often requires detailed knowledge of the magnitude and the structure of small-scale heterogeneity (e.g., Goltz and Roberts 1987;Li et al 1994;Di Federico et al 1999;LaBolle and Fogg 2001;Becker and Shapiro 2001;Guswa and Freyberg 2002;Zinn and Harvey 2003;Liu et al 2004;Zinn et al 2004).…”
Section: Introductionmentioning
confidence: 99%